PENGARUH LITERASI FINANSIAL TERHADAP KEBIASAAN MENABUNG. PERAN MEDIASI DARI KONTROL DIRI. STUDI PADA PENGUSAHA KECIL DAN MENENGAH DI KOTA KUPANG. - Maria Maria (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to investigate the direct and indirect effects of financial literacy on saving habits with the mediating role of self-control. Data were obtained from 84 small and medium entrepreneurs in Kupang City who were willing to act as respondents. Through a quantitative approach, the data obtained were then analyzed by means of multiple regression analysis. The results of this study indicate that financial literacy affects saving habits and is mediated by self-control. The practical benefits obtained can be utilized by small and medium-sized entrepreneurs to increase their ability to save.